INSPIRASI MENGINAP: Daya Tarik Media Sosial Instagram dalam Keputusan Tamu untuk Menginap di Aruss Hotel Semarang - Anggrean, Ricky; Wijoyo, Tuwuh Adhistyo (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The study employs a qualitative descriptive research method to thoroughly examine the influence of Instagram on guests' decisions to choose Arus Hotel Semarang for their stay. The key focus areas include the exploration of social media, particularly Instagram, and its impact on the decision-making process regarding accommodation. Through an in-depth analysis, the research delves into the implications and core findings, shedding light on how social media, with an emphasis on Instagram, plays a crucial role as a determining factor for guests opting to stay at Arus Hotel Semarang. The study aims to provide a detailed understanding of the specific features within Instagram that contribute positively to the decision-making process of potential guests, thereby highlighting the platform's significance in the realm of the hospitality industry, particularly in the context of Arus Hotel Semarang.